Recoding Art: Van Abbemuseum collection - Moreschi, Bruno; Pereira, Gabriel (Farol, 2020)
When Varèse lived in that street sixty years earlier, he was creating Poème Electronique, a commission from the Philips company. The eight-minutes song would become the soundtrack of the pavilion created by Le Corbusier at the 1958 Brussels World’s Fair. For this composition, Varèse gathered trivial sounds from Eindhoven, noises that would only be the disposable sounds of everyday life for many. But not the composer who, exhibiting keen attention and sensitivity, saw poetic power in these sounds and produced a striking composition. [...]